Kafā'ah dan Pemilihan Pasangan Generasi Z dalam Perspektif Al-Qur'an: Antara Otoritas Teks dan Otonomi Individu - Fatiya Nidaulhaq; Faisal Riza (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
Selecting a life partner is one of the most important decisions that has undergone significant transformation among Generation Z due to the development of digital technology and the growing emphasis on individual autonomy. In this context, the concept of kafā'ah in Islamic family law requires reexamination to remain relevant to contemporary social realities. This study aims to analyze the concept of kafā'ah from the Qur'anic perspective and reconstruct its relevance for Generation Z in choosing a life partner. This research employs a library research method using a thematic Qur'anic interpretation (mawḍū‘ī) approach combined with contextual analysis. The primary source is QS. Al-Nūr: 26, while secondary sources include classical and contemporary tafsir works, Islamic family law literature, and studies related to Generation Z. The analysis was conducted through textual examination of the verse, comparative analysis of exegetical interpretations, and contextualization within contemporary partner-selection practices in the digital era. The findings reveal that the Qur'anic concept of kafā'ah emphasizes moral and spiritual compatibility rather than social status equality. QS. Al-Nūr: 26 embodies three main principles: morality as the primary criterion of compatibility, equal responsibility between men and women, and kafā'ah as a continuous process of character formation. Based on these principles, this study reconstructs Qur'anic kafā'ah for Generation Z into four dimensions: religious compatibility, character compatibility, psychological compatibility, and life-goal compatibility. The study concludes that the Qur'anic concept of kafā'ah remains relevant as an ethical guideline for partner selection and serves as a bridge between religious textual authority and individual autonomy in the modern era.